New insights into the roles of lactylation in cancer - Yajun Zhu; Yajun Zhu; Wenhui Liu; Wenhui Liu; Zhiying Luo; Zhiying Luo; Feiyan Xiao; Bao Sun; Bao Sun (Frontiers in Pharmacology)
Lactylation, a novel discovered posttranslational modification, is a vital component of lactate function and is prevalent in a wide range of cells, interacting with both histone and non-histone proteins. Recent studies have confirmed that lactylation as a new contributor to epigenetic landscape is involved in multiple pathological processes. Accumulating evidence reveals that lactylation exists in different pathophysiological states and leads to inflammation and cancer; however, few mechanisms of lactylation have been elaborated. This review summarizes the biological processes and pathophysiological roles of lactylation in cancer, as well as discusses the relevant mechanisms and potential therapeutic targets, aiming to provide new insights for targeted cancer therapy.